CATEGORY OF MODALITY THROUGH CULTURAL CONCEPTS IN FICTIONAL PROSE (Conferencea, 2022)
The article is devoted to the study of cultural concepts in fictional prose. It reveals  the hidden peripheral characteristics of the “Queen” concept which  realizes  linguocultural   aspect of  category of  modality, analyzing examples from the works of these authors O. Wilde, G. Wells, O. Huxley